Assessment of microbial risks in the air of the Faculty of Engineering in Sabratha and its impact on health and safety (Al-Farooq Journal of Sciences, 2026)
Background: Indoor air quality (IAQ) in educational institutions significantly impacts public health and academic performance, yet bioaerosol dynamics in these environments remain understudied. This study evaluated airborne microbial loads and associated biological risks within the educational and administrative facilities of the Faculty of Engineering at Sabratha University.Methodology: Utilizing the passive sedimentation (settle plate) method, indoor air samples were systematically collected across 30 distinct locations, including classrooms, lecture halls, specialized laboratories, administrative offices, and restrooms. To capture a comprehensive microbiological profile, samples were inoculated onto three distinct culture media: Nutrient Agar, Blood Agar, and MacConkey Agar. Isolated strains were subjected to phenotypic identification and standardized antibiotic susceptibility testing.Results: Microbiological analysis revealed substantial bioaerosol contamination, with predominant growth observed on Nutrient Agar and Blood Agar. Phenotypic characterization confirmed the prevalence of Staphylococcus spp., Enterococcus spp., and Escherichia coli, alongside diverse airborne fungal assemblages. Conversely, MacConkey Agar exhibited zero growth across all sites, indicating a negligible baseline of robust, selective Gram-negative bacilli. Spatial distribution analysis demonstrated that restrooms and poorly ventilated administrative offices harbored the highest microbial densities. Furthermore, the density of Staphylococcus spp. correlated strongly with high anthropogenic occupancy in classrooms and lecture halls. Antibiotic susceptibility profiling indicated that the majority of bacterial isolates remained susceptible to frontline antimicrobial agents, displaying only marginal variations in resistance patterns.Conclusion: The findings demonstrate that IAQ within the faculty is dynamically driven by structural ventilation limitations, localized human density, and sanitation protocols. To mitigate potential bioaerosol-mediated health risks, this study underscores the critical need for optimizing mechanical ventilation exchange rates, implementing stringent, scheduled disinfection regimens, and establishing continuous microbiological air-monitoring programs.
Keywords: Indoor air quality; Bioaerosols; Microbial risk assessment; Anthropogenic occupancy; Ventilation efficiency; Sabratha.